Anisotropic propagation imaging of elastic waves in oriented columnar thin films. (8th November 2017) - Coffy, E; Dodane, G; Euphrasie, S; Mosset, A; Vairac, P; Martin, N; Baida, H; Rampnoux, J M; Dilhaire, S
Abstract: We report on the observation of strongly anisotropic surface acoustic wave propagation on nanostructured thin films. Two kinds of tungsten samples were prepared by sputtering on a silicon substrate: a conventional thin film with columns normal to the substrate surface, and an oriented columnar architecture using the glancing angle deposition (GLAD) process. Pseudo-Rayleigh waves (PRWs) were imaged as a function of time in x and y directions for both films thanks to a femtosecond heterodyne pump-probe setup. A strong anisotropic propagation as well as a high velocity reduction of the PRWs were exhibited for the GLAD sample. For the wavevector k /2 π = 3 × 10 5 m −1 the measured group velocities v x and v y equal 2220 m s −1 for the sample prepared with conventional sputtering, whereas a strong anisotropy appears ( v x = 1600 m s −1 and v y = 870 m s −1 ) for the sample prepared with the GLAD process. Using the finite element method, the anisotropy is related to the structural anisotropy of the thin film's architecture. The drop of PRWs group velocities is mainly assigned to the porous microstructure, especially favored by atomic shadowing effects which appear during the growth of the inclined columns. Such GLAD thin films constitute a new tool for the control of the propagation of surface elastic waves and for the design of new devices with useful properties.